2002
DOI: 10.1098/rspb.2001.1893
|View full text |Cite
|
Sign up to set email alerts
|

Polyandry produces sexy sons at the cost of daughters in red flour beetles

Abstract: Female mating with multiple males within a single fertile period is a common phenomenon in the animal kingdom. Female insects are particularly promiscuous. It is not clear why females mate with multiple partners despite several potential costs, such as expenditure of time and energy, reduced lifespan, risk of predation and contracting sexually transmitted diseases. Female red flour beetles (Tribolium castaneum) obtain sufficient sperm from a single insemination to retain fertility for several months. Nonethele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 38 publications
4
59
2
Order By: Relevance
“…In the absence of material benefits (e.g. food gifts, paternal care, access to resources), polyandrous females may produce fitter offspring through biasing paternity towards males with higher genetic quality, variability/ compatibility (Bernasconi et al 2003;Zeh & Zeh 2003) or with better sperm (Pai & Yan 2002). Courtship could provide a female with information about a male's genetic quality and females may base their decision as to which male to choose as a principal sire for her offspring on the courtship performance (Tallamy et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of material benefits (e.g. food gifts, paternal care, access to resources), polyandrous females may produce fitter offspring through biasing paternity towards males with higher genetic quality, variability/ compatibility (Bernasconi et al 2003;Zeh & Zeh 2003) or with better sperm (Pai & Yan 2002). Courtship could provide a female with information about a male's genetic quality and females may base their decision as to which male to choose as a principal sire for her offspring on the courtship performance (Tallamy et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Provided that there is enough genetic variance for mate quality (or compatibility), genetic benefits will always accompany any direct benefits ( Jennions & Petrie 2000;Fedorka & Mousseau 2002). Studies that have found some support for genetic benefits tested the prediction that polyandrous females should have fitter progeny than monogamous females (Madsen et al 1992;Olsson et al 1996;Watson 1998;Tregenza & Wedell 1998;Evans & Magurran 2000;Bernasconi & Keller 2001;Konior et al 2001;Fedorka & Mousseau 2002;Pai & Yan 2002;Sakaluk et al 2002;Kamimura 2003). However, the increased opportunity to choose a mate by polyandrous females could influence their investment in their progeny (Simmons 1987;Wedell 1996;Pearse et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…georgiana) do not benefit from polyandry in any environment [54] and polyandrous female decorated crickets (Gryllodes sigillatus) produce heavier sons independent of the environment [40]. It appears that the optimal mating strategy of the female yellow dung fly (Scathophaga stercoraria) and red flour beetle (Tribolium castaneum) are influenced by the environment experienced during early development and that only females producing offspring under certain conditions gain indirect benefits [55,56]. Further investigations are required to determine whether the costs or benefits of the mating change under variable ecological conditions and therefore whether the form and strength of selection for polyandry is temporally and spatially variable [7,57,58].…”
Section: Discussionmentioning
confidence: 99%